1992
DOI: 10.1017/s0021900200043023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Luria–Delbrück distribution using discrete convolution powers

Abstract: The Luria–Delbrück distribution arises in birth-and-mutation processes in population genetics that have been systematically studied for the last fifty years. The central result reported in this paper is a new recursion relation for computing this distribution which supersedes all past results in simplicity and computational efficiency: p 0 = e–m ; where m is the expected number of mutations. A new relation for the asymptotic behavior of pn (≈ c/n 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 10 publications
0
87
0
Order By: Relevance
“…To analyze the data, we employed a program written by P. J. Gerrish (Los Alamos National Laboratory) that generates expected Luria-Delbrü ck distributions according to the method of Ma et al (1992) and then uses maximum likelihood to refine the mutation rate estimate. This procedure gave a mutation rate of 4.2 3 10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the data, we employed a program written by P. J. Gerrish (Los Alamos National Laboratory) that generates expected Luria-Delbrü ck distributions according to the method of Ma et al (1992) and then uses maximum likelihood to refine the mutation rate estimate. This procedure gave a mutation rate of 4.2 3 10…”
Section: Resultsmentioning
confidence: 99%
“…Fitness was then calculated as the ratio of the realized growth rates of the two strains during their direct competition, and t-tests were performed to evaluate whether the measured fitness values differed significantly from the null hypothetical value of 1. (Lea and Coulson 1949;Ma et al 1992). Evolutionary dynamics of malT substitutions: The approximate time of origin and the subsequent dynamics of the malT mutations that were substituted in each focal population were investigated using a PCR-RFLP strategy with clones isolated from samples frozen at various generations during the longterm evolution experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Put differently, quantile and zero-class methods have some advantage when there is some uncertainty about the underlying model or when there are known simplifying assumptions that can introduce error. The formula presented here derives from the simplest model for the LDD (Lea and Coulson 1949), which makes a number of simplifying assumptions, such as exponentially distributed times between replication events (a Markovian birth process) ( Jones et al 1999;Kepler and Oprea 2001), probabilities expressed in infinite (nontruncated) series thereby assigning nonzero (albeit miniscule) probabilities to unrealistically large mutant numbers (Armitage 1952;Bailey 1964;Stewart et al 1990;Ma et al 1992;Zheng 1999), and no difference in growth rates between wild-type and mutant subpopulations ( Jones 1994;Jaeger and Sarkar 1995;Zheng 1999). In light of these simplifying assumptions, whose impact can sometimes be significant, it might ultimately be desirable to use the less accurate but more robust quantile or zero-class methods to complement the more accurate but less robust likelihood methods.…”
Section: Discussionmentioning
confidence: 99%
“…Jones truncates the sum at 100, which is adequate for values L # 70, but thus limits applicability of his tabulated median method results to protocols for which plating efficiency is greater than $5%. A more elegant solution to the problem of infinite summation appears in Ma et al (1992) and Jones et al (1999).…”
mentioning
confidence: 99%
“…Among the later contributions that enhanced our ability to analyze fluctuation experiments are those made by Lea and Coulson (1949), Armitage (1952), Crump and Hoel (1974), Mandelbrot (1974), Koch (1982), Stewart et al (1990), Ma et al (1992), Jones et al (1994), and many others found in a recent review (Zheng 1999). Rosche and Foster's (2000) critical comparison of the then existing methods is a useful guide for biologists.…”
Section: T He Fluctuation Test Protocol Devised Bymentioning
confidence: 99%